Triangulation clay bodies formulation for lapohan traditional pottery - Norhayati Ayob; Shamsu Mohamad; Sazmal Effendi Arshad (IPG Kampus Tengku Ampuan Afzan, 2021)
This study investigated traditional local clay in Kampung Selakan, Selakan Island. Traditional lapohan pottery uses the triangulation formula to define the body of the clay. The purpose of this research was to study the effect of gosong (local black sand) on the lapohan's properties as a solution to protect the market from decline as traditional Lapohan pottery is important for the preservation of heirloom heritage requires. In the experiment, 18 formulations used varied the composition of Selakan clay (SC) by introducing gosong (black local sand) from 2% to 18% of the weight percentages studied. The durability, water absorption and shrinkage of the clay body is tested for each sample. The higher gosong content has resulted in higher water absorption, low shrinkage, and stability. Experiment on the production of the firing temperature at 900°C. The effects of heat on the composition of clay were measured quantitatively and the interaction between the mechanical resistance and the components of the lapohan pottery clay body was tested. The result comparison shows that the best composition is obtained by adding gosong which generated pottery products with improved aesthetic workability of clay. A descriptive approach of qualitative analysis, including observation and in-depth interviews for written or visual data collection, will gather the necessary details for the report. The study's findings and significance indicate that traditional development of lapohan pottery in Selakan Island primarily involves awareness and technological usage of clay as a primary material, preparation of clay bodies, and adaptation for potters utilising local natural source.